Renal Collecting Duct Carcinoma: A Case Report - Oğuz, Fatih; Güneş, Ali; Beytur, Ali; Söylemez, Haluk; Katı, Bülent; Şamdancı, Emine (Fırat University, 2011)
Collecting duct carcinomas are seen extremely rare. In this report, a 9 years old girl, who admitted to our clinic with hematuria and left flank pain for three months, is presented. Abdominal ultrasonography (USG), computed tomography (CT) and magnetic resonance (MRI) revealed a lobulated, hypoechoic, solid mass lesion The mass was 3x2.5 cm in diameters and located at the left renal pelvis level. Left transperitoneal radical nephrectomy was performed. The histopathological diagnosis was collecting duct carcinoma (Bellini) of papillary tubular type. Immunohistochemically, neoplastic cells had positive immunoreactivity to cytokeratine-7 (CK-7), HMWCK and CEA. Reevaluation of the patient, other organs involvement and local recurrence was not detected. Collecting duct carcinomas (CDC) are seen extremely rare and have poor prognosis and their diagnosis are difficult.

Renal hücreli karsinomlar içerisinde toplayıcı duktal karsinomlar son derece nadir görülür. Bu çalışmada son üç aydır var olan sol yan ağrısı ve pıhtılı hematüri şikayetiyle başvuran 9 yaşında kız çocuğu sunulmuştur. Abdominal utrasonografi (USG), bilgisayarlı tomografi (BT), manyetik rezonans (MRI)' da sol böbrek renal pelvis düzeyinde 3 x 2,5 cm boyutda solid kitle lezyonu tespit edildi. Hastaya sol transperitoneal radikal nefrektomi uygulandı. Histopatolojik değerlendirmede; toplayıcı duktal karsinomun papiller tubüler tipi olarak rapor edildi. İmmünhistokimyasal incelemede; sitokeratin-7 (CK-7), HMWCK ve CEA ile immünreaktivite belirlendi. Hastanın kontrollerinde başka organ yayılımı ve lokal nüks saptanmadı. Toplayıcı duktal karsinomlar, son derece ender ve tanısı zor konulan tümörlerdir ve prognozu oldukça kötü seyretmektedir.
Böbrek Toplayıcı Tübül Kanseri: Olgu Sunumu